Globalization and Organization : World Society and Organizational Change - Edited By Gili S. Drori; Meyer, John W. and Hwang, Hokyu (New York Oxford University Press, 2006)
The process of globalization has meant the intensification of global interdependencies and the consolidation of the global as a social horizon, and this has provided fertile breeding grounds for new organizations and the elaboration of extinct ones, This book describes and analyzes these organizations, and the modern managerialism that has accompanied them, looking at such issues as management education, corporate governance, accounting, and human resource management. - ;The process of globalization has meant the intensification of global interdependencies and the consolidation of the global.
Include Index, biliography, and Abbrevations.
This book explores various dimensions of the trends of expansion, formalization, and standardization of organizing worldwide by exploring such organizational legacies as accounting, business management, corporate social responsibility, and performance benchmarks. Featuring contributions from prominent academics, the book argues that these processes can be attributed to globalization and to its specific tendencies of universalism, rationalization, and rise of the modern notion of the strongly bounded and purposive social actor.
Keywords: Organizational change -- Management